Freshwater resources around the reclaimed new land on the Eastern Hengsha Shoal in the Changjiang estuary - Wu, Tong; Zhu, Jianrong; Ma, Rui; Qiu, Wei; Yuan, Rui (Frontiers in Marine Science, 2023)
Reclaiming estuarine tidal flats is practiced to meet the growing demand for land. The reclaimed new land (RNL) on the Eastern Hengsha Shoal in the Changjiang Estuary is for agricultural production in Shanghai. Whether freshwater resources exist around the RNL has become a critical issue \caused by estuarine saltwater intrusion. In this study, the spatiotemporal saltwater intrusion and freshwater distribution around the RNL at different guarantee rates of river discharge using the improved 3D numerical model ECOM-si was investigated. Three water intakes on Hengsha Island and the northern edge of the RNL were set. The results showed that at different guarantee rates of river discharge during the dry season, there is a relatively sufficient suitable water intake time in the upper RNL. Nevertheless, there is a very limited suitable water intake time in the middle and lower RNL as the guarantee rate increases, especially in January and February. During the flood season, three water intakes can ensure sufficient suitable water intake time. The salinity around the RNL significantly increases under the combined effect of 50% and 95% guarantee rates with a 12 m/s northerly wind in February, resulting in a significant threat to the three water intakes. At the 50% guarantee rate, the suitable water intake times in February are 14.86, 9.78 and 3.53 days at three water intakes, respectively. At the 95% guarantee rate, the suitable water intake time in February is only 0.31 days in the upper RNL, and there is no freshwater in the middle and lower RNL. Overall, there is sufficient freshwater in the flood season and limited freshwater in the dry season for agriculture along the northern edge of the RNL.